Promoting Vocational School Students' Critical Thinking in Speaking by Using Instagram: Teachers’ Voices - Winny Berliana; Sri Setyarini; Nenden Sri Lengkanawati; Bachrudin Musthafa; Rojab Siti Rodliyah (STAI Hubbulwathan Duri, 2025)
The integration of digital tools in education has underscored the need for innovative strategies to develop critical skills, particularly in English as a Foreign Language (EFL) contexts. Among vocational school students, the ability to think critically and speak effectively in English is essential for employability and global communication. This qualitative study explored the use of Instagram to enhance critical thinking in speaking among vocational school students in Indonesia. Five EFL teachers, all experienced in using Instagram in the classroom, participated in the research. Data were collected through semi-structured interviews, classroom observations, and analysis of students' Instagram-based speaking activities. Thematic analysis was employed to identify key patterns and insights. Findings indicate that Instagram supports critical thinking development by encouraging students to analyze content, evaluate different viewpoints, and articulate arguments through speaking tasks. Students also demonstrated improved fluency and confidence. However, challenges such as digital distractions and varying levels of digital literacy emerged. Teachers highlighted the need for structured guidance and scaffolding to mitigate these issues. Instagram holds significant potential as a pedagogical tool for enhancing critical thinking in speaking within EFL vocational settings. Effective implementation requires intentional instructional design, including reflective questioning, peer feedback, and guided support. Future research should examine the long-term effects of social media-based learning on learners’ cognitive and linguistic progress.